Sustainable Approaches to Waste Management: Regulatory and Financial Instruments - Kutsevych , Maksym; Yara, Olena; Golovko, Liudmyla; Terpeliuk, Volodymyr (European Journal of Sustainable Development, 2020)
with the provisions and principles of EU waste policy and development of suggestions for improvement of Ukrainian law. The article provide an overview of EU waste legislation, main EU investment policy and its contributions to municipalities in the area of solid municipal waste management. The ways of ecological modernization of the management of solid municipal waste were investigated. Proposals for implementation of experience of EU member states, which has proved itself in practice, were made. Keywords: EU waste management, EU law, adaptation of Ukrainian legislation to EU standards, financial instruments